Characteristics of pulmonary cryptococcosis in patients with rheumatoid arthritis - Hosoda, Chiaki (BMJ Open Respir Res, 2021)
BACKGROUND AND OBJECTIVE: A high frequency of infections complicating rheumatoid arthritis (RA) has been reported due to the immunomodulatory effect of RA or to agents with immunosuppressive effects used in its treatment. We aimed to assess clinical and radiological characteristics of pulmonary cryptococcosis in patients with and without RA. METHODS: We retrospectively reviewed the medical records of 52 patients with pulmonary cryptococcosis and divided them into two groups, those with RA and without RA, and compared clinical characteristics and radiological findings between them. RESULTS: Eleven (21.2%) of the 52 patients had RA. Median follow-up periods were 51.2 (range: 1.1–258.7) months for patients with RA and 19.1 (range: 0.63–246.9) months for patients without RA. Among the patients with RA, 81.8% were women, with a mean age of 68.1 years. Female sex and respiratory comorbidities were significantly more frequent in patients with RA than in patients without RA. Frequencies of concomitant cryptococcal meningitis and respiratory failure were not different between the groups. There were no significant differences in frequency of any radiological findings, locations and number between the two groups. Among patients with RA, all but one responded well to antifungal treatment. During the antifungal treatment course, one (9.1%) patient with RA died of cryptococcosis. Despite continuing antirheumatic drugs, no patients had recurrence of pulmonary cryptococcosis during follow-up. CONCLUSION: Other than some differences in background, there were no clinical, radiological or prognostic differences between the patients with and without RA with pulmonary cryptococcosis. The administration of antirheumatic therapy had no negative effect on the clinical course of antifungal treatment.